ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL TRIGONOMETRI BERDASARKAN KRITERIA WATSON - Adinda Cahyani; Indrie Noor Aini (IKIP Siliwangi, 2021)
This study aims to analyze the mistakes made by students in solving trigonometric questions based on Watson's criteria. The research method used is descriptive qualitative method. The subjects studied in this study were students of class XI MIPA 1 in one of the public high schools in Karawang Regency. The sampling technique was purposive sampling. The instrument used in this study was a test instrument in the form of trigonometric questions. The data analysis techniques used were: data collection, data reduction, and conclusion drawing. The results of this study indicate that the location of the mistakes made by students is inappropriate procedures (IP), omitted data (od), omitted conclusions (oc), and skills hierarchy problems (SHP). The cause of students making incorrect procedural errors is not understanding the concept of solving problems and not understanding how to write down the process of solving steps, the cause of missing data errors is their inadequacy in presenting data that should be used, missing conclusions are inability to link data previously known / obtained to draw a conclusion, and the error of the skill hierarchy problem is the inaccuracy of students when calculating.